The Role of Attachment, Travel Experiences and English Proficiency in International Students’ Acculturative Stress and Depressive Symptoms - Smiljanic, Iskra (Journal of International Students, 2017)
This study examined the relationship between attachment, travel experiences, and English proficiency and international students’ acculturative stress and depressive symptoms. A total of 91 graduate international students completed online surveys. Pearson correlations showed that both attachment anxiety and avoidance were positively correlated with depressive symptoms, while only attachment anxiety was positively correlated with acculturative stress. Acculturative stress was significantly higher for those participants who never traveled abroad prior to moving to the US. Additionally, lower scores on the speaking section of the TOEFL exam were related to more acculturative stress. Implications for outreach, counseling, and future research are discussed.